Enhanced Recovery After Surgery for Noncolorectal Surgery?: A Systematic Review and Meta-analysis of Major Abdominal Surgery. Issue 1 (January 2018) - Visioni, Anthony; Shah, Rupen; Gabriel, Emmanuel; Attwood, Kristopher; Kukar, Moshim; Nurkin, Steven
Abstract : Objective: To evaluate the impact of enhanced recovery after surgery (ERAS) protocols across noncolorectal abdominal surgical procedures. Background: ERAS programs have been studied extensively in colorectal surgery and adopted at many centers. Several studies testing such protocols have shown promising results in improving postoperative outcomes across various surgical procedures. However, surgeons performing major abdominal procedures have been slower to adopt these ERAS protocols. Methods: A systematic review was performed using "enhanced recovery after surgery" or "fast track" as search terms and excluded studies of colorectal procedures. Primary endpoints for the meta-analysis include length of stay (LOS) and complication rate. Secondary endpoints were time to first flatus, readmission rate, and costs. Results: A total of 39 studies (6511 patients) met inclusion and exclusion criteria. Among them 14 studies were randomized trials, and the remaining 25 studies were cohort studies. Meta-analysis showed a decrease in LOS of 2.5 days (95% confidence interval, CI: 1.8–3.2, P < 0.001) and a complication rate of 0.70 (95% CI: 0.56–0.86, P = 0.001) for patient treated in ERAS programs. There was also a significant reduction in time to first flatus of 0.8 days (95% CI: 0.4–1.1, P < 0.001) and cost reduction of 5109.10 (95% CI: 4365.80–5852.40, P < 0.001). There was no significant increase in readmission rate (OR 1.03, 95% CI: 0.84–1.26, P = 0.80) in our analysis. Conclusions: ERAS protocols decreased length of stay and cost by not increasing complications or readmission rates. This study adds to the evidence that ERAS protocols are safe to implement and are beneficial to surgical patients and the healthcare system across multiple abdominal procedures. Abstract : Supplemental Digital Content is available in the text